2007
DOI: 10.1088/0960-1317/17/11/002
|View full text |Cite
|
Sign up to set email alerts
|

A micro optofluidic splitter and switch based on hydrodynamic spreading

Abstract: This paper presents the fabrication and characterization of a silicon-based optofluidic device for switching and splitting of a core stream with fluorescent dyes. The dye laser was created in the core, which is excited by a blue wavelength. The streams in the microchannel also form a liquid-core/liquid-cladding wave guiding system. The core is a glycerol solution, while the cladding is formed by two sheath streams of deionized water. The higher refractive index of the glycerol solution keeps the laser light in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 11 publications
0
32
0
2
Order By: Relevance
“…Furthermore, the basic elements of optical platforms have been developed with optofluidic principles, namely waveguides [88][89][90][91][92][93][94] and optical switches [95][96][97][98][99]. The optofluidic switch has even reached industrial level (Agilent Photonic Switching Platform).…”
Section: Optofluidic Platformsmentioning
confidence: 99%
“…Furthermore, the basic elements of optical platforms have been developed with optofluidic principles, namely waveguides [88][89][90][91][92][93][94] and optical switches [95][96][97][98][99]. The optofluidic switch has even reached industrial level (Agilent Photonic Switching Platform).…”
Section: Optofluidic Platformsmentioning
confidence: 99%
“…121,122 Such lenses have been used as manipulators of light exhibiting the ability to control the amplitude, phase, and polarization properties of light and its directions of propagation. [123][124][125][126][127] Beam control was demonstrated by displacing optically trapped particles such as an SiO 2 (Ø13 lm) microsphere through a light beam. beam to be refracted by various degrees as a function of the particle position, providing tuneable attenuation and beam-steering in the device.…”
Section: Particles As Lensesmentioning
confidence: 99%
“…Soft lithography technique was used to fabricate the microchannel in PDMS (Nguyen 2006). The layout shown in Fig.…”
Section: Design and Fabrication Of Test Devicesmentioning
confidence: 99%
“…The response time is an important parameter for switching techniques. Wolfe et al (2004) reported switching with a response time of 2 s. The response time reported by Campbell et al (2004) was 20 ms. Hydrodynamic switching reported by Nguyen et al (2007) has a response time of 0.3 s. Tan and Lee (2005) and Huh et al (2007) reported that microfluidic devices can be used to separate droplets using hydrodynamic effect. A cell counting and sorting system which can be used as cytometer was designed by Yang et al (2006), the cell can be sorted at a frequency of 120 cells min -1 .…”
mentioning
confidence: 99%